Prognostic Factors for Locally Advanced Cervical Cancer Treated With Neoadjuvant Intravenous and Transuterine Arterial Chemotherapy Followed by Radical Hysterectomy. Issue 8 (1st October 2013) - Tsubamoto, Hiroshi; Yamamoto, Satoshi; Kanazawa, Riichiro; Sakane, Riya; Honda, Okuto; Kobayashi, Kaoru; Shibahara, Hiroaki; Hirota, Shozo
Abstract : Objective: The aim of this study was to identify prognostic factors associated with neoadjuvant transuterine arterial chemotherapy (TUAC) followed by type III radical hysterectomy. Methods: The medical histories of patients with stage IB2 to IIB cervical cancer who received neoadjuvant TUAC between 1996 and 2009 at our institution were retrospectively reviewed. Results: Seventy-three patients received TUAC using cisplatin combined with intravenous nedaplatin, irinotecan, paclitaxel, or etoposide administration. Forty-seven patients (64%) had squamous cell carcinoma. The radiological response rate was 96% (95% confidence interval, 91%–100%). Radical hysterectomy was completed for 95% of enrolled patients. Examination of the resected cervical specimens showed that tumor cells were absent in 19 cases and stromal invasion was less than 3 mm in 7 cases. Among these 26 patients, 23 (32%) had pathologically negative pelvic lymph nodes and no recurrence during the follow-up period. The 5-year relapse-free survival and overall survival rates were 69% and 74%, respectively. Among 23 patients with recurrence or progressive disease, the median survival time after recurrence or progression was 12 months. In multivariate analysis, a tumor size of more than 60 mm and pathological positive lymph nodes were negative prognostic factors for overall survival. Conclusions: Tumor size, pathological response, and lymph node metastases were prognostic factors for cervical cancer. The high pathological response rate associated with TUAC makes it a promising treatment for bulky cervical cancer.